Institutionalised dreams the art of managing foreign aid - Drążkiewicz, Elżbieta (EASA series ;, 2020)
"Using examples from Poland, Elżbieta Drążkiewicz explores the question of why states become donors and individuals decide to share their wealth with others through foreign aid. She comes to the conclusion that the concept of foreign aid requires the establishment of a specific moral economy which links national ideologies and local cultures of charitable giving with broader ideas about the global political economy. It is through these processes that the faith in foreign aid interventions as a solution to global issues is generated. The book also explores the relationship linking a state institution with its NGO partners, as well as international players such as the EU or OECD"--